Risk Assessment Tools Other Than FMEA for Quality Improvement in the Construction Industry – An Overview - Sivapiran, N.; Murugesan, G. (AMC Indian Journal of Civil Engineering, 2025)
Quality is one among the most imperative aspects in all walks of life. Construction industry is no exemption. Effective project management guarantees that each aspect of the project aligns with the initial design and specifications. In fact, quality is the prime of all issues as human lives depend on the quality of the building. Emphasizing safety standards not only shelters workers but also contributes to the overall excellence of the construction process. For enhanced construction, risk free working environment is essential. There exists an array of tools to assess and thereby, reduce risk. Each tool has unique strengths and focuses on different aspects of risk and quality management. The authors have explored into the diverse risk assessment tools that may be adopted in the industry of construction.